(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
The objective of this study was to strengthen the critical thinking of eleventh grade students of an educational institution in Colombia, in the municipality of Madrid-Cundinamarca, through the approach of critical mathematics. The research was qualitative within the framework of action research. Four phases were carried out for the execution of the research: identification, understanding of the problem, reaction and reflection. The participants were interested in studying the situation generated by the Covid 19 pandemic, specifically with regard to vaccination in their immediate environment. It was possible to show that by involving in the mathematics classroom problems or situations with which the student feels identified, critical thinking is strengthened, since the participants became interested in a situation, deepened their understanding and reacted to it, specifically to confront false beliefs about vaccination.